Mouse ear edema modulation by different propolis ethanol extracts - Menezes, H.; Alvarez, J. M.; Almeida, E. (Ecv-editio Cantor Verlag Medizin Naturwissenschaften, 1999)
The anti-inflammatory activity of 14 commercial ethanol extracts of propolis were evaluated, using a mouse ear inflammation model induced by arachidonic acid. Indometacin was also assayed as standard anti-inflammatory agent. Different activities were observed and discussed. This model could be used to assess the anti-inflammatory quality of propolis extracts and facilitate their posological usage on skin edema resulting from wounds.
Keywords: anti-inflammatories; propolis, anti-inflammatory effect, mouse, quality control